#### Answer

{-3}

#### Work Step by Step

8x - 2 = 7x - 5
Step 1 : Collect variable terms on one side and constants on the other side.
subtract 7x from both the sides
8x - 2 - 7x = 7x - 5 -7x
Simplify
x - 2 = -5
Add 2 on both the sides
x -2 + 2 = -5 + 2
Simplify
x = -3
Now we check the proposed solution,-3 , by replacing x with -3 in the original equation.
Step 1: the original equation 8x - 2 = 7x - 5
Step2: Substitute -3 for x
8.(-3) - 2 = 7.(-3) - 5
Step 3: Multiply 8.(-3) = -24, 7.(-3) = -21
-24 - 2 = -21 -5
Step 4: Solve
-26 = -26
Since the check results in true statement, we conclude that the solution set of the given equation is {-3}